2017
DOI: 10.1007/s11864-017-0461-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategies for Metastatic Neuroendocrine Tumors of the Gastrointestinal Tract

Abstract: The therapeutic landscape of gastroenteropancreatic-neuroendocrine tumors (GEP-NETs) has evolved significantly in recent years. Current and emerging treatment options include somatostatin analogs, radiolabeled somatostatin analogs, the mTOR inhibitor everolimus, and the tyrosine kinase inhibitor sunitinib. Although high-quality data from phase III trials are lacking, cytotoxic agents are commonly used for the treatment of poorly differentiated neuroendocrine carcinomas and well-differentiated NETs originating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 66 publications
0
58
0
9
Order By: Relevance
“…Treatment and prognosis depends on the size, stage, grade, resectability, and distant metastasis. In most cases, a multimodality approach is the mainstay of care in advanced disease [18-22]. …”
Section: Introductionmentioning
confidence: 99%
“…Treatment and prognosis depends on the size, stage, grade, resectability, and distant metastasis. In most cases, a multimodality approach is the mainstay of care in advanced disease [18-22]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to these cytotoxic regimens, everolimus, an oral inhibitor of mechanistic target of rapamycin (mTOR) is a candidate for treating unresectable neuroendocrine tumors. Although mutations of mTOR pathway genes are infrequently detected in gastrointestinal neuroendocrine tumors, mTOR overexpression and its downstream activity are implicated in adverse clinical outcomes [62,63] . In RADIANT-4, a phase III trial, everolimus was demonstrated to be superior to placebo for improving the median progression-free survival with gastrointestinal or lung neuroendocrine tumors (11.0 and 3.9 months, respectively) [64,65] .…”
Section: Management Of Recurrent or Unresectable Tumorsmentioning
confidence: 99%
“…More recently, targeted therapies have evolved such as gastrin receptor antagonist YM022 (netazepide) to treat the gastrin-dependent ECL-based tumors GC type 1 and GC type 2 (73, 74). Telotristat etiprate blocks serotonin production by inhibiting tryptophan hydroxylase 1 and could be used to palliate symptoms from the carcinoid syndrome (71, 75). For widely metastatic, poorly-differentiated and local unresectable disease, platinum-based regimens remain therapy of choice while the newer target therapies inhibiting specific signaling molecules such as everolimus for mTOR and sunitinib to block tyrosine kinases are currently being tested in clinical trials (71, 76, 77).…”
Section: Treatments For Gi-netsmentioning
confidence: 99%